2015
DOI: 10.1093/annonc/mdv221
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring therapies—improving the management of early breast cancer: St Gallen International Expert Consensus on the Primary Therapy of Early Breast Cancer 2015

Abstract: The 14th St Gallen International Breast Cancer Conference (2015) reviewed new evidence on locoregional and systemic therapies for early breast cancer. This manuscript presents news and progress since the 2013 meeting, provides expert opinion on almost 200 questions posed to Consensus Panel members, and summarizes treatment-oriented classification of subgroups and treatment recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
1,193
4
81

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,565 publications
(1,298 citation statements)
references
References 116 publications
(131 reference statements)
20
1,193
4
81
Order By: Relevance
“…A meta‐analysis56 of a non‐randomized comparison between 3165 TM procedures with standard BCS in 5494 patients with unifocal cancers showed that the former significantly reduced rates of cancer margin positivity ( P < 0·001) and surgical re‐excisions ( P < 0·001). Recently, the St Gallen panel2 recommended a minimal acceptable surgical margin of ‘no ink on invasive tumour or DCIS’. Other interventions significantly reducing intraoperative tumour margin positivity have been described: digital specimen radiology ( P = 0·012 for digital versus conventional mammography)59, tumour margin cavity shaves60 and real‐time cancer margin assessments61 62.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A meta‐analysis56 of a non‐randomized comparison between 3165 TM procedures with standard BCS in 5494 patients with unifocal cancers showed that the former significantly reduced rates of cancer margin positivity ( P < 0·001) and surgical re‐excisions ( P < 0·001). Recently, the St Gallen panel2 recommended a minimal acceptable surgical margin of ‘no ink on invasive tumour or DCIS’. Other interventions significantly reducing intraoperative tumour margin positivity have been described: digital specimen radiology ( P = 0·012 for digital versus conventional mammography)59, tumour margin cavity shaves60 and real‐time cancer margin assessments61 62.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical surveillance informing cancer outcomes should optimally extend to at least 10 years2 3. The Association of Breast Surgery guidelines50 recommend a target of 5‐year breast cancer LRR rates of 5 per cent or less from diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A lack of timely access to supportive oncodermatology care during the immediate post-treatment transition period, when recommended follow-up consultations occur at 3-4-or 6-month intervals (Carlson et al, 2011;Coates et al, 2015;Senkus et al, 2015), may lead to inadequate management of long-lasting dAEs.…”
Section: Introductionmentioning
confidence: 99%